The role of intuition in the reflective practice of adult education - Vivian Wilson Mott (Adult Education Research Conference, 1994)
The purpose of this qualitative study was to explore the role of intuition in reflective adult education practice. While the study began with the assumption that intuition is deeply embedded in professional practice, the data further indicate that intuition aids in perception, guides practice, and enhances professional competence.